2016
DOI: 10.1002/2016gl068330
|View full text |Cite
|
Sign up to set email alerts
|

The stratospheric pathway for Arctic impacts on midlatitude climate

Abstract: Recent evidence from both observations and model simulations suggests that an Arctic sea ice reduction tends to cause a negative Arctic Oscillation (AO) phase with severe winter weather in the Northern Hemisphere, which is often preceded by weakening of the stratospheric polar vortex. Although this evidence hints at a stratospheric involvement in the Arctic‐midlatitude climate linkage, the exact role of the stratosphere remains elusive. Here we show that tropospheric AO response to the Arctic sea ice reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
127
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 137 publications
(150 citation statements)
references
References 37 publications
10
127
1
1
Order By: Relevance
“…The work by Sun et al (2015) showed that changes in sea ice can impact the midto-upper tropospheric and lower stratospheric circulation in an idealized model. This is supported by the results of Peings and Magnusdottir (2014), Kim et al (2014) and Nakamura et al (2016), among others, who identified a connection with the stratosphere. However, such studies were largely concerned with the response to low sea ice and did not explicitly consider the causes of low sea ice in the first instance.…”
Section: Introductionsupporting
confidence: 69%
“…The work by Sun et al (2015) showed that changes in sea ice can impact the midto-upper tropospheric and lower stratospheric circulation in an idealized model. This is supported by the results of Peings and Magnusdottir (2014), Kim et al (2014) and Nakamura et al (2016), among others, who identified a connection with the stratosphere. However, such studies were largely concerned with the response to low sea ice and did not explicitly consider the causes of low sea ice in the first instance.…”
Section: Introductionsupporting
confidence: 69%
“…The enhanced wave amplitude can lead to more poleward energy transport (Peixoto and Oort, ; Lee et al ., ), which in turn can weaken the mid‐latitude/Arctic thermal contrast. Not only limited in the troposphere, the enhanced upward propagating planetary‐scale waves may further penetrate into the stratosphere and decelerate the westerly in the stratosphere (Kim et al ., ; Sun et al ., ; Nakamura et al ., ).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…It is unclear whether low-top models are able to properly represent the stratospheric pathway through which autumn sea ice can affect the winter circulation (Nakamura et al, 2016;Sun et al, 2015;Zhang et al, 2017Zhang et al, , 2018. It is unclear whether low-top models are able to properly represent the stratospheric pathway through which autumn sea ice can affect the winter circulation (Nakamura et al, 2016;Sun et al, 2015;Zhang et al, 2017Zhang et al, , 2018.…”
Section: Discussionmentioning
confidence: 99%